A negotiation-based model of tax-induced transfer pricing - Johannes Becker; Ronald B. Davies (University College Dublin, UCD School of Economics, 2014)
We present a new model of tax induced transfer pricing as an alternative to the oft-used concealment model. Inspired by interviews with practitioners, we consider a large multinational firm which is audited by the tax authority in the high-tax location. When this country adjusts the transfer prices proposed by the firm, the low-tax location may dispute this decision and initiate negotiations. Since negotiations are costly, the high-tax location sets a transfer price that prevents the low-tax location from entering negotiations. We compare this model's predictions to those of the concealment model. The negotiation model replicates the predictions on the tax rate effects on transfer pricing, while adding new predictions. Profit shifting is expected to fall in the high-tax country's bargaining power and to rise in firm profits and domestic firm ownership in both countries. Most importantly, profit shifting occurs even if tax enforcement is perfect. We analyze the effects of an introduction of a common consolidated corporate tax base with formula apportionment and conclude that the negotiation model may change the perspective on such a policy. Specifically, strong countries with large bargaining power may find this reform unappealing.
Keywords: H25; H32; H87; 330; transfer pricing; Nash bargaining; tax avoidance; corporate taxation